Hydrogen Production from Synthesis Gas Using the Photosynthetic Bacterium Rhodospirillum rubrum - Najafpour, Ghasem; Younesi, Habibollah (ASEAN Journal of Chemical Engineering, 2005)
Production of biological hydrogen by anaerobic photosynthetic bacteria, specifically Rhodospirillum rubrum, from synthesis gas was successfully conducted at ambient temperature and pressure. The influence of initial acetate concentration as the substrate for microbial growth was investigated in a batch system. Series of experiments were conducted using serum bottles as bioreactor. The agitation rate and light intensity were adjusted at 200 rpm and 1,000 lux, respectively. The concentration of acetate as carbon source was varied from 0.5 to 3.0 g/I. It was observed that the increase in concentration of the carbon source from 2.5 to 3 g/l resulted in the decrease both in the growth of the microorganism and in hydrogen production rate. Experimental results showed that the optimum acetate concentration would be from 1 to 2 g/I. The resulting data also showed that in 1-2 g/I acetate, highest hydrogen formation and cell concentration were obtained. Additional acetate in the initial culture medium inhibited the growth of R. rubrum. An inverse relationship between acetate concentration and initial cell growth was observed. This article presents a method to calculate the mass transfer coefficient for gaseous substrates and the process parameters involved in a gas and liquid fermentation system. The procedure had been defined by experimental data for the bioconversion of CO to C02’ while H20 is converted into hydrogen. Hence, a biologically-based water-gas shift reaction provided an attractive alternative improvement for renewable resources to achieve higher hydrogen production. Keywords: Anaerobic bacteria, batch culture, coefficient, CO uptake rate, mass transfer, photobiological hydrogen, and Rhodospirillum rubrum.